Reactive Oxygen Species-Based Nanomaterials for Cancer Therapy - Li, Yingbo; Yang, Jie; Sun, Xilin (Frontiers in Chemistry, 2021)
Nanotechnology advances in cancer therapy applications have led to the development of nanomaterials that generate cytotoxic Reactive Oxygen Species (ROS) specifically in tumor cells. ROS act as a double-edged sword, as they can promote tumorigenesis and proliferation but also trigger cell death by enhancing intracellular oxidative stress. Various nanomaterials function by increasing ROS production in tumor cells and thereby disturbing their redox balance, leading to lipid peroxidation and oxidative damage of DNA and proteins. In this review, we outline these mechanisms, summarize recent progress in ROS-based nanomaterials, including metal-based nanoparticles, organic nanomaterials, and chemotherapy drug-loaded nanoplatforms, and highlight their biomedical applications in cancer therapy as drug delivery systems (DDS) or in combination with chemodynamic therapy (CDT), photodynamic therapy (PDT) or sonodynamic therapy (SDT). Finally, we discuss the advantages and limitations of current ROS-mediated nanomaterials used in cancer therapy and speculate on the future progress of this nanotechnology for oncological applications.